Modelling of Electrical Conductivity of a Silver Plasma at Low Temperature. (August 2016) - Andre, Pascal; Bussiere, William; Coulbois, Alain; Gelet, Jean-Louis; Rochette, David
Abstract: During the working of electrical fuses, inside the fuse element the silver ribbon first begins to melt, to vaporize and then a fuse arc appears between the two separated parts of the element. Second, the electrodes are struck and the burn-back phenomenon takes place. Usually, the silver ribbon is enclosed inside a cavity filled with silica sand. During the vaporization of the fuse element, one can consider that the volume is fixed so that the pressure increase appears to reach pressures higher than atmospheric pressure. Thus, in this paper two pressures, 1 atm and 10 atm, are considered. The electrical field inside the plasma can reach high values since the distance between the cathode surface and the anode surface varies with time. That is to say from zero cm to one cm order. So we consider various electrical fields: 10 2 V/m, 10 3 V/m, 5×10 3 V/m, 10 4 V/m at atmospheric pressure and 10 5 V/m at a pressure of 10 atm. This study is made in heavy species temperature range from 2, 400 K to 10, 000 K. To study the plasma created inside the electric fuse, we first need to determine some characteristics in order to justify some hypotheses. That is to say: are the classical approximations of the thermal plasmas physics justified? In other words: plasma frequency, the ideality of the plasma, the Debye-Hückel approximation and the drift velocity versus thermal velocity. These characteristics and assumptions are discussed and commented on in this paper. Then, an evaluation of non-thermal equilibrium versus considered electrical fields is given. Finally, considering the high mobility of electrons, we evaluate the electrical conductivities.